2016
DOI: 10.15171/joddd.2016.038
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mast cell counts and microvessel density in reactive lesions of the oral cavity

Abstract: Background. Reliable immunohistochemical assays to assess the definitive role of mast cells (MCs) and angiogenesis in the pathogenesis of oral reactive lesions are generally not available. The aim of the present study was to evaluate mast cell counts (MCC) and microvessel density (MVD) in oral reactive lesions and determine the correlation between MCC and MVD.Methods. Seventy-five cases of reactive lesions of the oral cavity, including pyogenic granuloma, fibroma, peripheral giant cell granuloma, inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The outcome of mutual mast cell‐fibroblast interactions promotes granulation tissue formation, a hallmark of PG, 18 which encouraged us to evaluate the mast cells numbers in both histopathological subtypes. Several authors 19 have found a positive correlation between the number of microvessels and mast cells in a group of so‐called reactive lesions, including LCH, fibrous hyperplasia, inflammatory fibrous hyperplasia, and peripheral giant cell lesion, while others found a negative correlation 20 . In our study, we found a positive, yet not significant correlation between microvessels and mast cells, similar to previous results, 18 and no difference in the number of mast cells between groups.…”
Section: Discussionsupporting
confidence: 91%
“…The outcome of mutual mast cell‐fibroblast interactions promotes granulation tissue formation, a hallmark of PG, 18 which encouraged us to evaluate the mast cells numbers in both histopathological subtypes. Several authors 19 have found a positive correlation between the number of microvessels and mast cells in a group of so‐called reactive lesions, including LCH, fibrous hyperplasia, inflammatory fibrous hyperplasia, and peripheral giant cell lesion, while others found a negative correlation 20 . In our study, we found a positive, yet not significant correlation between microvessels and mast cells, similar to previous results, 18 and no difference in the number of mast cells between groups.…”
Section: Discussionsupporting
confidence: 91%
“…Kouhsoltani et al. (2016) also showed that MC T expression was higher in gingival tissue below the epithelial surface compared to deep connective tissue. There are few studies in the literature on the histochemistry of MCs enzymes for neutral serine proteases in the tongue.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, MC T s have been identified in the skin of felines in both the subepidermal and deep dermis (Noli et al, 2003). Kouhsoltani et al (2016)…”
Section: Mast Cell Subtypes Mean ± Semmentioning
confidence: 99%
“…The outcome of mutual mast cell-fibroblast interactions promotes granulation tissue formation, a hallmark of PG [55], which encouraged us to evaluate the mast cells numbers in both histopathological subtypes. Several authors [56], have found a positive correlation between the number of micro vessels and mast cells in a group of so-called reactive lesions, including LCH, fibrous hyperplasia, inflammatory fibrous hyperplasia, and peripheral giant cell lesions, while others found a negative correlation [57]. The major basic protein of eosinophils has proangiogenic effects and may participate in inflammation and tissue remodeling.…”
Section: Etiopathogenesismentioning
confidence: 99%

Oral Pyogenic Granuloma: A Narrative Review

Lomeli Martinez,
Carrillo Contreras,
Gómez Sandoval
et al. 2023
IJMS